Colonization of Helicobacter pylori–like organisms on the ectopic gastric mucosa of Meckel’s diverticulum:A case report* - Mehmet A. DEMİR and Ali R. KANDİLOĞLU and Semin AYHAN (Turkish Journal of Gastroenterology, 2019)
-